Hubungan Kualitas Pelayanan Rumah Sakit dengan Kepuasan Pasien Rawat Inap di Rumah Sakit - Maria Lintang; Sri Endang (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
One aspect that needs to be considered in medical record services in the registration section in order to have good quality is the quality of service of officers in providing medical record documents. Medical record services provided in the registration section are registration services, searching and distributing medical records, the Methods used, namely literature review, can be used to understand and describe the current state of research in fields related to the topic under study. The results showed that there was a positive and significant relationship between service quality and patient satisfaction in the hospital, the Relationship between Hospital Service Quality and Patient Satisfaction in Hospitals is a concept that shows that the quality of service provided by the hospital affects the level of patient satisfaction. The results showed that there is a positive and significant relationship between service quality and patient satisfaction in the hospital. Conclusion In the research conducted, there are patients who are dissatisfied with hospital services and patients who are satisfied with hospital services. This shows that the quality of service provided by the hospital affects the level of patient satisfaction. Therefore, it is important for hospitals to improve the quality of services provided in order to increase patient satisfaction and provide better health services.